Six years of measuring patient experiences in Belgium: Limited improvement and lack of association with improvement strategies. - Astrid Van Wilder; Kris Vanhaecht; Dirk De Ridder; Bianca Cox; Jonas Brouwers; Fien Claessens; Dirk De Wachter; Svin Deneckere; Dirk Ramaekers; Else Tambuyzer; Ilse Weeghmans; Luk Bruyneel (PLoS ONE, 2020)
Objective To examine trends in patient experiences in the period 2014-2019, describe improvement strategies implemented by hospitals in the same period, and study associations between patient experiences and implemented strategies. Design Multi-center retrospective region-wide observational design. Setting Flanders, Belgium. Participants 44 out of 46 Flemish acute-care hospitals publicly reporting patient experiences via the Flemish Patient Survey (FPS). Main outcome measure(s) Primary outcomes were the two global FPS ratings: percentage of patients rating the hospital 9 or 10 and percentage of patients definitely recommending the hospital. Secondary outcomes were the average top-box score percentages for each of the 8 remaining dimensions of the FPS. Results Between 2014 and 2019, there was a significant improvement in patients scoring the hospital 9 or 10 (56% to 61%) and patients definitely recommending (67% to 70%) the hospital. Significant increases in patient experiences over time were also observed in other dimensions, except for the dimension discharge. Hospital key informants reported various improvement strategies related to patient experiences with care and the FPS. Feedback to nursing wards (n = 44, 100%) and clinicians (n = 39, 89%) were most common. Overall, most improvement strategies were not or only weakly associated with patient experience ratings in 2019 and changes in ratings over time. Still, positive associations were discovered between the strategies 'nursing ward interventions' and 'hospital wide education' and recommendation of the hospital. Conclusions Patient experiences have improved modestly in Flemish acute-care hospitals. Hospitals report to have invested in patient experience improvement strategies but positive associations between such strategies and FPS scores are weak, although there is potential in further exploring nursing ward interventions and hospital wide education. Hospitals should continue their efforts to improve the patient's experience, but with a more targeted approach, taking the lessons learned on the efficacy of strategies into consideration.